Two‐step method for calculation of eddy current losses in a laminated transformer core. Issue 9 (3rd June 2020) - Frljić, Stjepan; Trkulja, Bojan
Abstract : A method for calculating eddy currents and corresponding losses in a laminated transformer core using finite element method is developed. The method is based on the transformation of the 3D model into the corresponding 2D model. The 2D laminated domain coincides with the slice of the 3D laminated domain. Eddy currents are therefore considered as 2D phenomena within lamination, instead of the 1D approximation, thus taking into account the edge effects. By using the 2D mesh, the number of finite elements is drastically reduced. The validity and precision of the method are verified by comparing the results of the simulation with the results obtained using the brute force approach and with the results obtained using the homogenisation method.